The Impact of Recent European Developments on Operation of the Rule of Law Principle in the Czech Republic - Janderová, Jana (NISPAcee press, 2019)
The rule of law principle is an essential basis of European administrative law as an interpretative concept of the exercise of public powers in the EU and its member states. It is a broad principle encompassing substantial number of sub-principles impacting both the legislator and also the administrative bodies. The later ones must act only within their powers and only for proper purposes. Administrative bodies are subject to control as to whether their acts are in conformity with the applicable laws as the prerequisite for the rule of law proper operation is a system of independent judiciary review. The paper focuses mainly on the principle of legality and proportionality as the key elements of rule of law and their interpretation by the Czech administrative courts. Relevant case law is analysed and compared to the interpretation provided by the Court of Justice of the EU and the European Court of Human Rights. The paper summarizes how the recent developments on the European level affected the operation of rule of law in the Czech Republic.
Vliv aktuální evropské judikatury na fungování principu právního státu v České republice
Keywords: Administrative Justice; Europeanization; Good Governance; Legality; Proportionality; Rule of Law; Správní soudnictví; Europeizace; Dobrá správa; Zásada zákonnosti; Právní stát